Implementasi Tata Kelola Teknologi Informasi di Lingkungan Institusi Akademik Menggunakan Framework Cobit 2019 pada Universitas XYZ - Mambu, Joe Yuan; Sanger, Alan Hubert Frederick; Lengkong, Andreuw Vandy; Sondakh, Debby Erce; Pungus, Stenly Richard (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
This research aims to evaluate and enhance IT governance at Universitas XYZ by implementing the COBIT 2019 framework. The study acknowledges the growing significance of technology in operational efficiency and productivity. IT governance ensures the alignment of IT with organizational goals, managing resources, and mitigating risks. The methodology includes collecting primary and secondary data through observations, interviews, and document analysis. The research framework focuses on 11 design factors of COBIT 2019, assessing Universitas XYZ’s IT capabilities and identifying gaps. Findings reveal that Universitas XYZ prioritizes cost leadership and innovation, with a strong focus on quality financial information. The risk profile indicates substantial impact areas like IT investment and operational incidents, while the role of IT is classified as critical yet not fully integrated into strategic innovation. The IT sourcing model leans towards outsourcing, and traditional implementation methods are predominant. The study identifies APO10 (Managed Vendor Relationships) and BAI01 (Managed Program) as priority objectives. The capability levels for these objectives indicate areas for improvement, particularly in vendor management. The research concludes with recommendations for enhancing IT governance through strategic resource allocation and staff development, aiming to elevate Universitas XYZ’s IT maturity and competitive edge.